Study on pore structure and fractal characteristics of fractured coal based on mercury injection and low temperature nitrogen adsorption tests - Siliang CHEN; Zebiao JIANG; Xiping QUAN; Xifa YANG; Qiaoshun MO (Meikuang Anquan)
In order to study the effect of cracking on the pore microstructure of coal rock, low-temperature nitrogen adsorption meth-od and mercury injection method were used to study the pore morphology and pore size distribution of coal samples before and after cracking, and then the fractal dimension of pores in different ranges was calculated based on the data of low-temperature nitrogen and mercury injection combined with the fractal theory. The results show that the pore volume of coal samples increases after cracking. The large pore volume of cracked coal is 1.4−2.2 times that of raw coal, and the micropore volume is 3.7−8.2 times that of raw coal. The fractal dimension of raw coal’s seepage pore and adsorption pore is greater than that of cracking coal at pressure less than 13.8 MPa and low pressure zone, and the fractal dimension of raw coal’s diffusion pore is smaller than that of cracking coal at pressure more than 13.8 MPa but less than 137.9 MPa and high pressure zone.